COOPERATIVE ASYNCHRONOUS INTERACTION IN VIRTUAL LEARNING - Suárez Guerrero, Cristobal Nico (2014)
The main objective of this research is to deepen our understanding of the concept of cooperative interaction under conditions of asynchronous mediation in virtual learning. The study starts with the basic assumption that technology is not a neutral component in an interaction (Person–Machine–Person). It follows; therefore, that a change in the way of perceiving interaction may be created by the way manoeuvrability is facilitated via the internet and the framework of virtuality. The research methodology examines the cooperative asynchronous interaction as two different but complementary processes. The initial, theoretical exploration is designed to understand the psychological, pedagogical and technological factors under which cooperation in virtual learning is generated. The subsequent, empirical exploration is designed to observe –via a triangulation of the data– how the cooperative interaction in learning groups using discussion boards to communicate in an asynchronous way, may be built into a university-level virtual learning experience.